2023
DOI: 10.7759/cureus.36391
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Moroccan Arabic Version of the Pediatric International Knee Documentation Committee Score (Pedi-IKDC) Questionnaire for Children With Knee Disorders

Abstract: BackgroundThe Pedi International Knee Documentation Committee (Pedi-IKDC) is a questionnaire for the evaluation of knee function in children and adolescents with knee disorders. It has been translated and validated into many languages. The aim of this study was to translate this questionnaire into Moroccan Arabic and evaluate its psychometric properties in a pediatric population. MethodsThe original English version of the questionnaire was translated into Moroccan Arabic according to international guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Psychometric property testing has been conducted on the Pedi-IKDC questionnaire in various languages, including English (Original) [ 2 , 7 ], Danish [ 20 ], Dutch [ 8 ], Italian [ 21 ], Portuguese [ 22 ], Spanish [ 23 ], and Moroccan [ 6 ]. In all of these studies, Cronbach’s α was found to be 0.91, 0.9, 0.92, and 0.94 for English [ 2 , 7 ], Danish [ 20 ], Italian [ 21 ], and Portuguese [ 22 ], respectively, demonstrating similar levels of internal consistency as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychometric property testing has been conducted on the Pedi-IKDC questionnaire in various languages, including English (Original) [ 2 , 7 ], Danish [ 20 ], Dutch [ 8 ], Italian [ 21 ], Portuguese [ 22 ], Spanish [ 23 ], and Moroccan [ 6 ]. In all of these studies, Cronbach’s α was found to be 0.91, 0.9, 0.92, and 0.94 for English [ 2 , 7 ], Danish [ 20 ], Italian [ 21 ], and Portuguese [ 22 ], respectively, demonstrating similar levels of internal consistency as observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there are differences between the daily and sporting activities of children and adults [ 5 ]. Third, asking questions regarding activity levels according to age is necessary [ 6 ]. Fourth, parental help may be required to complete the questionnaire.…”
Section: Introductionmentioning
confidence: 99%